Penentuan Status Mutu Kualitas Air Sungai Somber Hulu Menggunakan Metode Indeks Pencemaran - Basransyah Basransyah; Rina Noor Hayati; Melisa Triandini Maulani; Mawan Eko Defriatno (LPPM ITK, 2026)
Population growth that is not balanced with adequate environmental management can hurt environmental quality. The Somber Hulu River is one of the rivers located in the North Balikpapan District. Some people living around the river directly discharge liquid waste into the river, potentially causing pollution that can disrupt the river ecosystem. One sign of pollution in the Somber Hulu River is characterized by smelly and cloudy river water. The research began by determining the river water sampling point, and then the water samples were tested to determine the pollutant concentration based on the specified parameters. The next stage was determining the water quality status using the Pollution Index (IP) method. The reference water quality standard used the class II river water quality standard based on Government Regulation number 22 of 2021. The purpose of this study was to determine the water quality status in the Somber Hulu River as a basis for decision-making in planning control measures to improve surface water quality. Based on the results of the measurements carried out, it is known that in general the water quality of the Somber Hulu River is moderately polluted with an IP value of 3.87 and lightly polluted with an IP value of 7.05 at point 2, an IP value of 5.37 at point 3, and an IP value of 5.25 at point 4. There needs to be management and control of water pollution sources, such as optimizing the use of septic tanks, carrying out monitoring activities, conducting routine river water quality monitoring, and encouraging community involvement in sustainable river management.